Peculiar age distribution of cytogenetic abnormalities in acute myeloid leukemia - E. W. Fleischman; O. I. Sokova; A. V. Popa; O. P. Kirichenko; L. N. Konstantinova; N. F. Metelkova (Онкогематология, 2022)
Peculiar age distribution of clinically significant recurring chromosome abnormalities was found as a result of investigation of526AML patients (249 children and 277 adults). Thus t(8;21) was more frequently detected in age from 2 to 10 years, t(15;17) was extremely rare in children under 5 years, rearrangements of 11q23 region were observed in more than half of patients under 24 months, inv(16) was most characteristic for patients in age 16-20 years; patients who were older than 51 years have showed a comparatively high incidence of normal karyotype (no chromosome abnormalities).There were defined some chromosome characteristics of AML observed in children in age under 24 months. No patients with normal karyotype and chromosome translocations t(8;21) and t(15;17) associated with good risk were detected, but 11q23 rearrangements and complex karyotype were found significantly more frequent than in older children and adults.Cytogenetic features of AML in different age groups with their hematopoietic peculiarities can be useful for clarification of mechanisms of specific chromosome abnormalities origin.